Pendekatan Hierarki Kebutuhan Maslow pada Motivasi Pembelian Electric Vehicles di Indonesia - Rahardi, Rafi Amani Muflih; Rachmawati, Indira (Image : Jurnal Riset Manajemen, 2023)
The transportation sector is one of the largest contributors to the greenhouse effect. This causes consumers and industry to look for solutions to reduce the greenhouse effect, one of them is an Electric Vehicles (EV). EV is considered as one of the responses to reduce the use of oil energy and carbon emissions from the transportation sector. However, the EV success depends on the level of people's need for EV. Maslow's hierarchy of needs is widely used to understand consumer buying motivation and consumer buying behavior. This study aims to determine EV Purchase Motivation in Indonesia by using Maslow's Hierarchy of Needs approach. Questionnaires from 385 respondents were then analyzed using multiple linear regression models. Based on the research, the Openness to Experience variable has the most significant effect on EV Purchase Motivation, followed by Environmental Concern, Price Consciousness, and Self Esteem. Meanwhile, the Social Influences variable has a negative and insignificant effect on EV Purchase Motivation.. From a practical point of view, there are several useful recommendations for the government and also advice to automotive marketers and manufacturers.